2013
DOI: 10.5812/jjm.7866
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Surveillance of Norovirus Diarrhea in Hospitalized Children with Acute Gastroenteritis in South of Iran

Abstract: Background: Noroviruses are one of the most common causes of acute diarrhea in both developed and developing countries. They are responsible for more than 50% of all gastroenteritis outbreaks around the world.Objectives: This study was conducted to assess the prevalence, seasonality and clinical characteristics of norovirus infection in hospitalized Iranian children.Patients and Methods: Between 2008 and 2010, a cross-sectional descriptive study was conducted on 375 stool samples from children under 7 years of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
2
1
1
Order By: Relevance
“…The most commonly associated clinical symptom observed in this study with rotavirus, adenovirus, and norovirus positive cases was “vomiting” with 55.6%, 55.8%, and 75.0%, respectively. This finding is similar to other studies [ 23 – 25 ] where vomiting was the most commonly associated symptom with viral diarrhea. Rotavirus positive patients with respect to clinical symptoms such as fever, dehydration, and abdominal pain were low in this study compared to other studies [ 23 , 26 , 27 ] which reported high percentage of clinical symptoms.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The most commonly associated clinical symptom observed in this study with rotavirus, adenovirus, and norovirus positive cases was “vomiting” with 55.6%, 55.8%, and 75.0%, respectively. This finding is similar to other studies [ 23 – 25 ] where vomiting was the most commonly associated symptom with viral diarrhea. Rotavirus positive patients with respect to clinical symptoms such as fever, dehydration, and abdominal pain were low in this study compared to other studies [ 23 , 26 , 27 ] which reported high percentage of clinical symptoms.…”
Section: Resultssupporting
confidence: 92%
“…Similarly, for adenovirus positive patients, fever, dehydration, and abdominal pain were low compared to other studies with moderate symptoms [ 13 , 24 , 28 , 29 ]. However, as regards norovirus positive patients, fever, dehydration, and abdominal pain were also low, but other studies with norovirus showed moderate to high clinical symptoms [ 25 , 30 , 31 ]. Thus, the differences in clinical symptoms with viral diarrhea as seen from the different studies may be attributed to seasonal variations, geographical location, nutritional status of the patients, and type of viral pathogens causing the infection.…”
Section: Resultsmentioning
confidence: 95%
“…In the report, most commonly reported symptoms were diarrhea, fever, vomiting, abdominal pain in virus-infected patients. These findings are in accordance with those conducted in South of Iran, Venezuela, Spain, Hungary and in Brasil were found fever and lymphocytosis to be significantly higher in adenovirus-rotavirus co-infected patients (40,41) Clinically, it would be difficult to separate viral gastroenteritis from gastroenteritis caused by other microorganism particularly, bacterial gastroenteritis. Molecular methods raised the overall diagnostic efficacy by 10%, and by 2.5% each for adenovirus and rotavirus (10).…”
Section: Discussionsupporting
confidence: 90%
“…We will check the suggested reference and revise our manuscript accordingly. Our study result showed higher norovirus infection incidence than previous studies mentioning incidence about 17 13 We involve 94 subjects in this study and 31 subjects (32.9%) were norovirus positive. We will revise our manuscript.…”
Section: Hirokazu Kimuracontrasting
confidence: 45%